Webies in Cyberspace - Jelisaveta Safranj (Journal of Language Research, 2018)
An exploratory piece discusses linguistic phenomena of 'webies' in cyberspace, considering morphology, semantics, and social usage patterns in online communication.
Keywords: Webies